Investigación de la prueba de la acidez como parámetro clasificatorio de rechazo o aceptación de la leche materna en mujeres que acuden a donar al banco de leche del hospital general provincial docente de riobamba durante el período de febrero 2015 a julio 2015. - Johanna Katherine, Aldás Tapia (2015)
This research work used to test the acidity as Qualifier parameter of rejection or acceptance of breast milk in women who come to donate to the milk bank of Provincial General Hospital of Riobamba during the period February 2015 to July 2015, for the realization of this work has the support of the theoretical framework based on clinical criteria, norms and standards applied for classification and acceptability of breast milk consumption of children requiring this well so appreciated.